Carbon in the Coastal Seascape: How Interactions Between Mangrove Forests, Seagrass Meadows and Tidal Marshes Influence Carbon Storage - Huxham, M.; Whitlock, D.; Githaiga, M.; Dencer-Brown, A. (Springer, 2018)
Purpose of Review We use the ‘seascape’ concept to explore how interactions between mangrove forests, tidal marshes and seagrass influence the storage of carbon in these ecosystems. Mangrove forests, with the other two ‘blue carbon’ habitats, are exceptionally powerful carbon sinks. Maintaining and enhancing these sinks is an emerging priority in climate change mitigation. However, managing any one ecosystem on its own risks is ignoring important contextual drivers of carbon storage emerging from its place in the seascape. We consider how interactions between these coastal habitats directly or indirectly affect the amounts of carbon they can store. Recent Findings The export of carbon from seagrasses may occur over hundreds or thousands of kilometres, much further than reported for mangroves or tidal marshes. Seagrasses may buffer mangroves from wave impacts, assisting forest regeneration. Trophic cascades supported by contiguous blue carbon habitat may limit excessive herbivory and bioturbation in them but evidence is limited. Summary Direct transfers of carbon between blue carbon habitats are common and are likely to enhance total carbon storage, but our understanding of their contribution to carbon stocks at the seascape level is elementary. There is evidence for indirect enhancement of carbon storage at the seascape by close association of habitats, mostly through the creation and maintenance of propitious conditions by one ecosystem for another. Protection from waves of mangroves by seagrass and protection from excess nutrients and sediment of seagrass by mangroves and tidal marsh are key mechanisms. There is little evidence or theory suggesting negative effects on carbon storage of one blue carbon habitat on another
Human and Animal Rights Statement All reported studies/experiments with human or animal subjects performed by the authors have been previously published and complied with all applicable ethical standards (including the Helsinki declaration and its amendments, institutional/ national research committee standards and international/national/institutional guidelines).
Keywords: Mangrove; Seagrass; Tidal marsh; Carbon; Seascape; Sequestration